151 TISSUE OXYGENATION DURING INFUSION OF VASOACTIVE AGENTS IN NEW ZEALAND RABBITS. Issue 1 (1st January 2007) - Uppal, A.; Lee, J.; Kim, J.; Tran, A.; Ju, J.; Burney, T.; Tseng, L.; Krueter, K.; Mukai, D.; Mahon, S.; Brenner, M.
Abstract : Background: Dobutamine, norepinephrine, and phenylephrine are used in the treatment of shock. The primary goal of resuscitation is improved tissue oxygenation; clinically applicable methods to assess adequacy of resuscitation at the tissue level are indirect at this time. Diffuse optical spectroscopy (DOS) is a noninvasive technology capable of direct assessment of tissue oxygenation. In this study, the feasibility of monitoring tissue oxygenation using DOS was assessed during infusion of vasoactive agents. Methods: Four New Zealand rabbits were intubated and mechanically ventilated. Femoral arterial and venous lines were placed for blood pressure monitoring and blood sampling. Dobutamine, norepinephrine, and phenylephrine were infused in sequence. Each infusion lasted 5 to 10 minutes and was followed by a 10-minute washout period. Blood pressure and venous blood gases were monitored. DOS was used to measure tissue hemoglobin, deoxyhemoglobin, oxyhemoglobin, oxygen saturation, and cytochrome oxidation state. Results: All three vasoactive agents caused MAP and VO2 to increase from baseline. DOS measurements revealed an increase in tissue oxyhemoglobin and tissue oxygen saturation during infusion. This finding reflects increased tissue oxygenation, which correlated with VO2 measurements. Conclusion: DOS measurements of tissue oxygenation correlated with VO2 measurements. DOS shows potential as a noninvasive means of directly monitoring tissue oxygenation, which could be used to guide decisions regarding optimization of vasoactive agent administration.